Intergenerational transmission of relative deprivation: A moderated mediation model. (January 2021) - Xuan, Zheli; Gao, Fengqiang; Zhou, Yuci; Wang, Hongxiu; Zhao, Jinzhe; Han, Lei; Luo, Jing
Highlights: The intergenerational transmission effect of relative deprivation was discovered. Children's sense of security played a mediator role. Teachers' emotional support played a moderator role. Positive family factors and school factors were indispensable. Abstract: To explore the intergenerational transmission of relative deprivation, as well as the mediating role of children's sense of security and the moderating role of teachers' emotional support, questionnaires were used in this study. Considering the family as the sampling unit, 271 families of junior high school students were surveyed. The results showed that the relative deprivation of parents significantly predicted that of their children, and there was an intergenerational transmission effect. Moreover, the sense of security partially mediated the intergenerational transmission of relative deprivation. Finally, teachers' emotional support moderated the path by which relative deprivation of parents affected children's sense of security. For children with a high level of teachers' emotional support, relative deprivation of parents had a significant and negative predictive effect on their sense of security; Conversely, for children with a low level of teachers' emotional support, relative deprivation of parents had no significant effect. The results suggested that the relative deprivation of children was the result of the combined effect of teachers' emotional support and parents' relative deprivation, and both factors were indispensable. Only when parents and teachers provided positive guidance and support for the development of adolescents could they truly protect children from relative deprivation and foster their healthy growth.